Differences between magnitudes and health impacts of BC emissions across the United States using 12 km scale seasonal source apportionment - Turner, Matthew D; Henze, Daven K; Hakami, Amir; Zhao, Shunliu; Resler, Jaroslav; Carmichael, Gregory R; Stanier, Charles O; Baek, Jaemeen; Sandu, Adrian; Russell, Armistead G; Nenes, Athanasios; Jeong, Gill-Ran; et al. (Environmental science & technology, 2015)
Recent assessments have analyzed the health impacts of PM2.5 from emissions from different locations and sectors using simplified or reduced-form air quality models. Here we present an alternative approach using the adjoint of the Community Multiscale Air Quality (CMAQ) model, which provides source-receptor relationships at highly resolved sectoral, spatial, and temporal scales. While damage resulting from anthropogenic emissions of BC is strongly correlated with population and premature death, we found little correlation between damage and emission magnitude, suggesting that controls on the largest emissions may not be the most efficient means of reducing damage resulting from anthropogenic BC emissions. Rather, the best proxy for locations with damaging BC emissions is locations where premature deaths occur. Onroad diesel and nonroad vehicle emissions are the largest contributors to premature deaths attributed to exposure to BC, while onroad gasoline emissions cause the highest deaths per amount emitted. Emissions in fall and winter contribute to more premature deaths (and more per amount emitted) than emissions in spring and summer. Overall, these results show the value of the high-resolution source attribution for determining the locations, seasons, and sectors for which BC emission controls have the most effective health benefits.
Keywords: benzin; Seasons; teoretické modely; výfukové emise vozidel; monitorování životního prostředí; lidé; Vehicle Emissions; roční období; saze; Mortality, Premature; Gasoline; Spojené státy americké; Air Pollutants; Soot; Environmental Monitoring; United States; látky znečišťující vzduch; Models, Theoretical; předčasná smrt; Humans